Effect of Adding an Organic Binder on Health of Cows Fed with Mycotoxins Contaminated Diet - Adami Ghamsari, F; Tajabadi Ebrahimi, M; Bagheri Varzaneh, M; Iranbakhsh, A; Akhavan Sepahi, A (Journal of the Hellenic Veterinary Medical Society, 2023)
Mycotoxins contamination occurring in dairy cow’s diet is responsible for devastating effects on livestock health. Among different strategies, using organic adsorbents is a promising approach to reduce the toxicity of mycotoxins. This study investigated the effects of an organic adsorbent containing Lactobacillus brevis TD4, Lactobacillus paracasei TD3, and Saccharomyces cerevisiae cell wall on milk production, somatic cell count, blood parameters (white blood cell [WBC], lymphocyte [LYM], neutrophil, basophil, monocyte, eosinophil, red blood cell, haemoglobin, haematocrit, mean corpuscular volume, mean corpuscular haemoglobin) and liver function (alanine transaminase [ALT], gamma-glutamyl transferase [GGT], aspartate transaminase [AST], alkaline phosphatase [ALP], urea, total protein, albumin) in dairy cows fed a naturally contaminated diet with Zearalenone and Deoxynivalenol. The amounts of mycotoxins Zearalenone (ZEA) and Deoxynivalenol (DON) in feed ingredients were measured using the HPLC method. Ten Holstein dairy cows received organic adsorbents daily in their diets for four weeks. Milk and blood samples were taken from cows before the start of feeding adsorbent (CTRL), during the feeding period (FP), and one week after removal of adsorbent from the diet (RP). Totally, the amount of measured ZEA and DON toxins in the diet were 389 and 1254.6 ppb, respectively. Feeding of organic adsorbent significantly increased milk production, total serum protein, and albumin compared to CTRL (P<0.01). Also, numerically lower somatic cell count in their milk and a significant decrease (P<0.01) in serum urea were resulted. Among examined blood parameters, the number of WBC and LYM significantly decreased (P<0.01) after feeding with the organic binder in comparison to the control period. Furthermore, except for a significant increase in the level of AST (P<0.05), the other liver function examined parameters were not affected. The consumption of feed containing low-cost organic adsorbent including Lactobacillus bacteria and yeast cell wall can improve the physical condition and health of dairy cows and reduce economic losses in livestock production.